Effects of the COVID-19 Pandemic and Telehealth on Antenatal Screening and Services, Including for Mental Health and Domestic Violence: An Australian Mixed-Methods Study - Henry, Amanda; Yang, Jennifer; Grattan, Sarah; Roberts, Lynne; Lainchbury, Anne; Shanthosh, Janani; Cullen, Patricia; Everitt, Louise (Frontiers in Global Women's Health, 2022)
Introduction Australian antenatal care includes specific screening and service provision for domestic and family violence (DFV) and mental health. However, the COVID-19 pandemic resulted in major care changes, including greatly expanded telehealth. Given difficulties in a safe assessment and management of disclosures via telehealth, DFV and mental health service provision might be substantially impacted. This study therefore aimed to assess COVID-19 effects on DFV and mental health screening, as well as broader service provision from the perspective of local maternity service providers. Methods Mixed-methods study of staff surveys and interviews of staff directly involved in pregnancy care (doctors, midwives, and allied health) in three Sydney (Australia) maternity units, from October 2020 to March 2021. Surveys and interviews interrogated perceived effects of the COVID-19 pandemic on delivery (ensuring required services occurred), timeliness, and quality of (a) overall maternity care and (b) DFV and mental health screening and care; and also advantages and disadvantages of telehealth. Surveys were descriptively analyzed. Interviews were conducted online, recorded, and transcribed verbatim prior to thematic analysis. Results In total, 17 interviews were conducted and 109 survey responses were received. Breakdown of survey respondents was 67% of midwives, 21% of doctors, and 10% of allied health. Over half of survey respondents felt the pandemic had a negative effect on delivery, timeliness, and quality of overall pregnancy care, and DFV and mental health screening and management. Perceived telehealth positives included convenience for women (73%) and reducing women's travel times (69%). Negative features included no physical examination (90%), difficulty regarding non-verbal cues (84%), difficulty if interpreter required (71%), and unsure if safe to ask some questions (62%). About 50% felt telehealth should continue post-pandemic, but for <25% of visits. Those perceived suitable for telehealth were low-risk and multiparous women, whereas those unsuited were high-risk pregnancy, non-English speaking, and/or mental health/psychosocial/DFV concerns. “Change to delivery of care” was the central interview theme, with subthemes of impact on mental health/DFV screening, telehealth (both positive and negative), staff impact (e.g., continuity of care disruption), and perceived impact on women and partners. Discussion While telehealth may have an ongoing, post-pandemic role in Australian maternity care, staff believe that this should be limited in scope, mostly for low-risk pregnancies. Women with high risk due to physical health or mental health, DFV, and/or other social concerns were considered unsuited to telehealth.